2020
DOI: 10.1126/scisignal.aba4200
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic activation of an oxidative stress–dependent NRF2-p53 signaling network in breast epithelial spheroids and premalignancies

Abstract: Breast and mammary epithelial cells experience different local environments during tissue development and tumorigenesis. Microenvironmental heterogeneity gives rise to distinct cell regulatory states whose identity and importance are just beginning to be appreciated. Cellular states diversify when clonal three-dimensional (3D) spheroids are cultured in basement membrane, and one such state is associated with stress tolerance and poor response to anticancer therapeutics. Here, we found that this state was joint… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 155 publications
(196 reference statements)
0
22
0
Order By: Relevance
“…The main TF that promotes Hmox1 expression is the nuclear factor erythroid 2-related factor 2 (NRF2), that coordinates the basal and stress-induced activation of several cytoprotective genes, controlling key components of the cellular antioxidant system [ 30 ]. Both NRF2 and p53 regulate the expression of proteins involved in the protection against oxidative stress, and it has been suggested that there is a crosstalk between them [ 31 , 32 ], even though this interplay is not completely understood. Moreover, a link between p53 and NRF2 was described in multiple tumorigenic scenarios like lung and breast cancer [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main TF that promotes Hmox1 expression is the nuclear factor erythroid 2-related factor 2 (NRF2), that coordinates the basal and stress-induced activation of several cytoprotective genes, controlling key components of the cellular antioxidant system [ 30 ]. Both NRF2 and p53 regulate the expression of proteins involved in the protection against oxidative stress, and it has been suggested that there is a crosstalk between them [ 31 , 32 ], even though this interplay is not completely understood. Moreover, a link between p53 and NRF2 was described in multiple tumorigenic scenarios like lung and breast cancer [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a link between p53 and NRF2 was described in multiple tumorigenic scenarios like lung and breast cancer [ 33 , 34 ]. Furthermore, NRF2 deficits are buffered by compensatory increases in p53 signaling, and striking ROS-dependent phenotypes arise when both pathways are perturbed in breast-mammary epithelia [ 32 ]. In the context of stem cells, NRF2 overexpression protects mesenchymal stem cells against cell death caused by oxidative stress and preserves multi-differentiation potential [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NRF2 links oxidative conditions with DDR through the p21 protein which is encoded by CDKN1A and is mainly involved in cell cycle arrest [ 34 ]. NRF2 can induce the transcription of the CDKN1A gene which is also under the transcriptional control of TP53 [ 77 ]. Through a feed forward loop, enhanced levels of p21 compete with NRF2 for binding to its KEAP1 repressor, hence inducing the activation of the NRF2 pathway [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…The spatially heterogeneous trigger of JUND cluster genes in MCF10A spheroids is coordinated by two stress-responsive transcription factors NRF2 (nuclear factor erythroid 2 like 2, NFE2L2) and p53 (TP53) [49]. NRF2 and p53 play important roles in oxidative stress handling in normal mammary epithelia.…”
Section: Metabolic Regulators Heterogeneously Activated In 3d Mcf10a Spheroidsmentioning
confidence: 99%
“…In normal breast epithelial tissue and basal-like premalignancy, NRF2-p53 coordination provides an oxidative stress-handling network [49]. NRF2-mediated tolerance in premalignancy may permit the emergency of missense p53 mutations that drive the progression of TNBC.…”
Section: Tnbc-specific Metabolic Signaturesmentioning
confidence: 99%